TRIPS and India: An Analysis - Dr. Hilal Ahmad (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2008)
Recent changes in India’s patent policy indicate a paradigm shift in seeking greater protection of intellectual property rights. On one hand, this has given rise to fears being expressed over the impending collapse of local firms; on the other, there is optimism amidst expectation of a large increase in patent activity of domestic actors. This paper analyses the development of Trade Related Intellectual Property Rights (TRIPS) and how India is responding to it. India does not have many options as it is committed to implement the agreement on TRIPS of WTO. All India can do is buy time and implement IPRS in phased manner so that it can safeguard the Indian interest and give some time to Indian industries to invest and develop its research and development work.